THE DETERMINATION OF METEOROIDS' LIFE TIME UNDER ACTION OF PHOTONS AND PROTONS - Tikhomirova, E. N. (Одеські астрономічні публікації, 2007)
The life time of meteor streams under action of photons and protons is estimated. The interval of time after which the particles of the comet 9P(1867 G1)/Tempel 1(after bombarding the comet during the mission “Deep Impact”)reach the Earth is estimated...